Cuts Deep - Johnson, Catherine (Evans Brothers Ltd, 2007)
Devon is heading for trouble. He and his mates jack from other kids. They need the money. It's no big deal. Then Devon meets Savannah, and everything changes. He starts to change$1! = (BBut Devon's past is about to catch up with him. And nothing will ever be the same again...s
Keywords: Juvenile Fiction